Combined metabolomics and proteomics to reveal beneficial mechanisms of Dendrobium fimbriatum against gastric mucosal injury - Sun, Jing; Liu, Peng-Fei; Liu, Jia-Ni; Lu, Cong; Tong, Li-Tao; Wang, Yong-Quan; Liu, Jia-Meng; Fan, Bei; Wang, Feng-Zhong (Frontiers in Pharmacology, 2022)
As a dietary and medicinal plant, Dendrobium fimbriatum (DF) has been widely utilized in China for improving stomach disease for centuries. However, the underlying mechanisms against gastric mucosal injury haven’t been fully disclosed. Here, metabolomics and proteomics were integrated to clarify the in depth molecular mechanisms using cyclophosphamide-induced gastric mucosal injury model in mice. As a result, three metabolic pathways, such as creatine metabolism, arginine and proline metabolism, and pyrimidine metabolism, were hit contributing to Dendrobium fimbriatum protective benefits. Additionally, γ-L-glutamyl-putrescine, cytosine, and thymine might be the eligible biomarkers to reflect gastric mucosal injury tatus, and Dendrobium fimbriatum anti-gastric mucosal injury effects were mediated by the so-called target proteins such as Ckm, Arg1, Ctps2, Pycr3, and Cmpk2. This finding provided meaningful information for the molecular mechanisms of Dendrobium fimbriatum, and also offered a promising strategy to clarify the therapeutic mechanisms of functional foods.